¿Qué hago con mi hijo? What should I do with my child? (Journal of Parents and Teachers, 2026)
Guidance for parents on how to deal with three different situations in their children: fear of the dark, being left-handed, and hearing problems. It emphasises the importance of addressing the child's feelings first, rather than the problem itself, focusing on what they are feeling. Fears must be understood and dealt with through support, never through punishment. It highlights the importance of detecting problems in children as early as possible in order to promote learning, integration and full development.
Keywords: Fears, childhood, support, understanding, early intervention, and acceptance.